2023
DOI: 10.1186/s12906-023-03841-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial analysis of honey against Staphylococcus aureus isolates from wound, ADMET properties of its bioactive compounds and in-silico evaluation against dihydropteroate synthase

Abstract: Background One of the main challenges of wound healing is infection with multi-drug resistant (MDR) bacteria such as Staphylococcus aureus. The spectrum of antibiotics used to treat them is declining; thus, there is a need for alternatives. Our study was designed to evaluate the antimicrobial properties of honey, its pharmacokinetics (ADMET) properties and in-silico analysis of its bioactive compounds against dihydropteroate synthase of S. aureus using trimethoprim as control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A study in Ethiopia demonstrated that honey had antibacterial activity against tetracycline-resistant S. aureus and MRSA [93,94] . The antibacterial activity of honey could be due to its composition of various chemicals [1,52,58,[95][96][97] . As such, honey may be a potential therapy for infections caused by resistant strains of bacteria such as MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Ethiopia demonstrated that honey had antibacterial activity against tetracycline-resistant S. aureus and MRSA [93,94] . The antibacterial activity of honey could be due to its composition of various chemicals [1,52,58,[95][96][97] . As such, honey may be a potential therapy for infections caused by resistant strains of bacteria such as MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking has emerged as the most utilized in-silico or computational approach for studying interactions between proteins and other macromolecules with small lead drug compounds [51] [22] [23]. We docked a total of 13 ligands and trimethoprim against dihydropteroate synthase of E. coli and the docking scores for the various ligands ranged from − 4.0 to -5.3(kcal/mole while trimethoprim gave a docking score of -6.5 kcal/mole.…”
Section: Discussionmentioning
confidence: 99%
“…The stored isolates were rst sub-cultured using freshly prepared nutrient agar and incubated overnight at 37 o C. The isolates were then suspended each in sterilized 5 ml peptone water and the concentration of the isolates adjusted to MacFarland standard which holds approximately 10 7 cells/ml. From each standardized inoculum, 1 ml was plated out using surface plating technique on freshly prepared Mueller-Hinton agar and incubated for 1 h. After incubation, holes were bored aseptically as previously reported [23] and various concentrations of the extracts (100, 50 25 and 12.5%) and trimethoprim (100, 50, 25 and 12.50 mg/l) freshly prepared were dispensed in triplicates per plate and incubated at 37 o C overnight. The resulting zones were measured and interpreted as sensitive, intermediate and resistant as previously reported [34].…”
Section: Microbiological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Honey's bioactive components have been connected to its health-promoting and nutritional properties. Honey seems to have antioxidant, anticancer, anti-inflammatory, antimicrobials well as antidiabetic, anti-obesity, and woundhealing properties [3][4][5][6][7][8][9][10] and have been used and proposed against viral diseases such as the COVID-19 virus [11,12]. In animal and human models, honey has effects on the cardiovascular system and has been revived as a therapy for gastrointestinal diseases, and asthma [13][14][15].…”
Section: Introductionmentioning
confidence: 99%